Rapid and sensitive detection of antibiotic resistance on a programmable digital microfluidic platform. Issue 14 (18th June 2015) - Kalsi, Sumit; Valiadi, Martha; Tsaloglou, Maria-Nefeli; Parry-Jones, Lesley; Jacobs, Adrian; Watson, Rob; Turner, Carrie; Amos, Robert; Hadwen, Ben; Buse, Jonathan; Brown, Chris; Sutton, Mark; et al.
Abstract : An automated, rapid and sensitive detection system for antibiotic resistance encoding genes on an active matrix digital microfluidic platform. Abstract : The widespread dissemination of CTX-M extended spectrum β-lactamases among Escherichia coli bacteria, both in nosocomial and community environments, is a challenge for diagnostic bacteriology laboratories. We describe a rapid and sensitive detection system for analysis of DNA containing the bla CTX-M-15 gene using isothermal DNA amplification by recombinase polymerase amplification (RPA) on a digital microfluidic platform; active matrix electrowetting-on-dielectric (AM-EWOD). The devices have 16 800 electrodes that can be independently controlled to perform multiple and simultaneous droplet operations. The device includes an in-built impedance sensor for real time droplet position and size detection, an on-chip thermistor for temperature sensing and an integrated heater for regulating the droplet temperature. Automatic dispensing of droplets (45 nL) from reservoir electrodes is demonstrated with a coefficient of variation (CV) in volume of approximately 2%. The RPA reaction is monitored in real-time using exonuclease fluorescent probes. Continuous mixing of droplets during DNA amplification significantly improves target DNA detection by at least 100 times compared to a benchtop assay, enabling the detection of target DNA over four-order-of-magnitude with a limit of detection of a single copy within 15 minutes.